Afriat and Revealed Preference Theory - Diewert, W. E. (Review of Economic Studies, 1973)
Journal Article Afriat and Revealed Preference Theory Get access W. E. Diewert W. E. Diewert University of British Columbia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 3, July 1973, Pages 419–425, https://doi.org/10.2307/2296461 Published: 01 July 1973